2007
DOI: 10.1029/2006wr005293
|View full text |Cite
|
Sign up to set email alerts
|

Relating low‐flow characteristics to the base flow recession time constant at partial record stream gauges

Abstract: Base flow recession information is helpful for regional estimation of low‐flow characteristics. However, analyses that exploit such information generally require a continuous record of streamflow at the estimation site to characterize base flow recession. Here we propose a simple method for characterizing base flow recession at low‐flow partial record stream gauges (i.e., sites with very few streamflow measurements under low‐streamflow conditions), and we use that characterization as the basis for a practical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 13 publications
0
68
0
Order By: Relevance
“…Some studies have linked slopes b to the spatial scale and found that a linear relationship for storage-outflow (b = 1) was suitable for hillslopes but turned more and more into non-linear behavior (b > 1) with increasing catchment scale and catchment heterogeneity (Clark et al, 2009;Harman et al, 2009). We found no systematic pattern between slopes b and catchment area (not shown), although area often has been identified as a catchment characteristic for regional low-flow regression models (Eng and Milly, 2007). This may be due to the non-characteristic results of a RAM caused by aquifer heterogeneity (Rupp and Selker, 2005;Harman et al, 2009) or the unknown number of aquifers that contribute recession streamflow to each catchment (Ajami et al, 2011).…”
Section: The Effect Of Different Rams To Distinguish Catchments' Recementioning
confidence: 81%
“…Some studies have linked slopes b to the spatial scale and found that a linear relationship for storage-outflow (b = 1) was suitable for hillslopes but turned more and more into non-linear behavior (b > 1) with increasing catchment scale and catchment heterogeneity (Clark et al, 2009;Harman et al, 2009). We found no systematic pattern between slopes b and catchment area (not shown), although area often has been identified as a catchment characteristic for regional low-flow regression models (Eng and Milly, 2007). This may be due to the non-characteristic results of a RAM caused by aquifer heterogeneity (Rupp and Selker, 2005;Harman et al, 2009) or the unknown number of aquifers that contribute recession streamflow to each catchment (Ajami et al, 2011).…”
Section: The Effect Of Different Rams To Distinguish Catchments' Recementioning
confidence: 81%
“…Juston et al (2009) demonstrate that, if selected in an intelligent way, a small fraction of data points in a longer time series might contain almost all information of the entire data series. Eng and Milly (2007) found that "a single pair of strategically timed streamflow measurements" considerably improved the estimation of base flow recession coefficients compared to estimates based on catchment area. Rode et al (2007) applied a water quality model to the Elbe River and found that a subset of the entire calibration data provided good results.…”
Section: Prediction Of Ungauged Basins (Pub)mentioning
confidence: 99%
“…There is considerable controversy over the assumption that watersheds exhibit a fixed time constant, known as the baseflow recession constant, in the relation between aquifer storage and baseflow discharge (Zecharias and Brutsaert, 1988;Troch et al, 1993;Vogel and Kroll, 1996;Wittenberg, 1999;Eng and Milly, 2007;Harman and Sivapalan, 2009). Thus, another goal of our study is to improve our ability to construct hypothesis tests which can effectively evaluate whether or not watershed recessions are characterized by a time constant known as the baseflow recession constant, K b .…”
Section: Introductionmentioning
confidence: 99%